2015
DOI: 10.1093/jxb/erv212
|View full text |Cite
|
Sign up to set email alerts
|

Amylopectin biosynthetic enzymes from developing rice seed form enzymatically active protein complexes

Abstract: HighlightStarch biosynthetic enzymes in rice endosperm are physically associated with each other and form enzymatically active multiple protein–protein complexes, several of which were common to cereals while others were unique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
156
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(164 citation statements)
references
References 72 publications
4
156
0
Order By: Relevance
“…Based on our findings in this work and published results (32)(33)(34)(35), we now propose a RS biosynthetic pathway (Fig. 6).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Based on our findings in this work and published results (32)(33)(34)(35), we now propose a RS biosynthetic pathway (Fig. 6).…”
Section: Discussionsupporting
confidence: 74%
“…It is known that the SSIIIa protein is associated with other proteins in developing rice endosperm (32), and in maize a proportion of SSIIIa is also present in a large complex including ADP-glucose pyrophosphorylase (AGPase), pyruvate orthophosphate dikinase (PPDK), SSIIa, and SBEIIa and SBEIIb (33). The enzyme PPDK catalyzes a reversible reaction from pyruvate, ATP, and Pi to phosphoenolpyruvate (PEP), AMP, and PPi (34), but in photosynthesis, it operates in the direction of PEP formation, driven by the hydrolysis of PPi (34).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the question about whether the different molecular structures in TRS heterogeneous starch granules originated from the different dosages of the three SBE isoforms was raised. In addition, the fact that SBEs were inhibited gradually along with endosperm development in TRS supported this idea again ( A series of biochemical evidence has shown that SBEs are prone to forming a great variety of multisubunit complexes with SSs, DBEs, and Pho1 in the soluble fraction of amyloplasts in order to function (Hennen-Bierwagen et al, 2008Crofts et al, 2015). This fact, coupled with the complexity of starch development, makes it difficult to quantity SBEs that act directly on starch formation in TRS heterogeneous granules.…”
Section: Dynamic Deposition Of Amylopectin Biosynthetic Enzymes In Thmentioning
confidence: 86%
“…However, the loss of SBEI in a SBEIIb-deficient background in maize caused increased branching of amylopectin [287], and the researchers postulated that this result was suggestive of a regulatory role for SBEI in influencing the catalytic activity of other SBE isoforms. Indeed, physical interactions between SBEI and SBEIIb have been reported in endosperm amyloplasts from a number of sources [288][289][290][291]. SBEI's role in determination of amylopectin structure may be rather more subtle, as suggested by one recent study showing reduced germination efficiency of SBEI-deficient maize kernels [292].…”
Section: Branch Linkage Formation By Starch Branching Enzymesmentioning
confidence: 99%